Exploration of Climate Change on Mental Health in Indonesia: Systematic Analysis Review - Alfrisa Renuat; Muhammad Arkan Muhadzib; Depy Eka Rachmawati (Universitas Muhammadiyah Surakarta, 2024)
Currently, the world is facing a serious challenge in the form of climate change. Climate change gives rise to more devastating weather anomalies and natural disasters. The impact can be felt directly through physical and indirect damage felt by humans, one of which is mental health problems. Climate change also poses a threat to sustainable development in Indonesia. In the 2021 Climate Transparency report , it is reported that Indonesia's climate is in the